Anxiety as a psychological factor in futsal athlete performance - Aditya Athaariq Putra; Rivan Saghita Pratama (Sriwijaya Journal of Sport, 2025)
Research Problem: Anxiety is one of the psychological factors that can affect the performance of athletes during a match, including in futsal. Research Objective: This study aimed to analyse the anxiety level of male futsal athletes of the Semarang State University Student Activity Unit before competing. Method: This study uses descriptive quantitative methods through surveys. The study used 25 samples of male futsal athletes selected by total sampling. Data were collected using the Sport Competition Anxiety Test (SCAT), containing 15 questions.  Results: The results showed that 11 athletes (44%) had low levels of anxiety, while 14 athletes (56%) had moderate levels of anxiety. None of the athletes were included in the high anxiety category. Conclusion: Based on the findings, it can be concluded that anxiety is a significant psychological factor influencing the performance of futsal athletes. Moderate levels of anxiety can have a positive impact by enhancing focus, alertness, and mental readiness in high-pressure situations. In contrast, excessive anxiety negatively affects motor skills, concentration, and decision-making, ultimately reducing overall performance quality. Therefore, appropriate psychological interventions, such as stress management training and relaxation techniques, are essential to help athletes effectively manage anxiety and maintain optimal performance during competition.